Why Parental Unemployment Matters for Children's Educational Attainment: Empirical Evidence from The Netherlands. (2nd February 2019) - Mooi-Reci, Irma; Bakker, Bart; Curry, Matthew; Wooden, Mark
Abstract: This study examines the effect of parents' unemployment on their children's subsequent educational attainment. Its theoretical significance lies on its focus to test the mediating role of parents' changing work ethics during spells of unemployment. Integrating multiple survey and administrative data sources, our estimates are based on a sample of Dutch children ( n = 812) who were exposed to their parents' unemployment during the previous economic crisis in the early 1980s. Our results reveal a direct negative effect between fathers' unemployment duration and their children's educational attainment and also an indirect effect through mothers' changing attitudes towards work. We also find empirical evidence that mothers' and fathers' whose views about work become more pessimistic lead to reduced educational attainment among their children.